CUSTOMERS USING DIGITAL WALLET PLATFORMS AS A METHOD OF PAYMENT IN WEST JAKARTA - Samuel, Sylvia; Widjaja, Daniel (Universitas Pelita Harapan, 2022)
One form of electronic payment is the e-wallet. In Indonesia, many e-wallet products are available from both the public and private sectors. DANA is an e-wallet program that has previously received authorization from the Bank of Indonesia as a supplier of an e-wallet platform and as a digital financial institution. In 2018, DANA was introduced, and in its first four months, it attracted a million members. This study aimed to identify the variables that influence West Jakarta's adoption of DANA as an alternative payment method. Data were collected via a Google form online survey. Social networking sites like Instagram, Line, and internet discussion boards shared the link. DANA subscribers who reside in West Jakarta made up the respondents. In roughly two months, the data were gathered. This study included 187 respondents using SPSS as a tool for data filtering and multiple regression analysis. The findings suggested that perceived usefulness, perceived credibility, and subjective norm are the main factors influencing whether or not DANA will be accepted. All of these criteria significantly influenced users' decisions to utilize DANA.